Implementasi Blended Finance sebagai Alternatif Pendanaan bagi Lembaga Pembiayaan Ekspor Indonesia (LPEI) - Moreno Paskala Firdaus (Jurnal Manajemen Bisnis Era Digital, 2024)
Indonesia Eximbank (LPEI), as a state-owned enterprise under the Ministry of Finance, has a primary focus on export financing. However, LPEI is currently facing challenges in implementing sustainable finance. Sustainable finance is part of the environmental, social, and governance (ESG) roadmap aimed at achieving the 17 Sustainable Development Goals (SDGs). To address these challenges, this report aims to provide a financing alternative aligned with ESG principles. Blended finance was chosen as an appropriate alternative due to its inclusive and collaborative principles, which align with sustainable finance. Additionally, blended finance is expected to address the investment gap in the sustainable sector. By applying this scheme, LPEI can enhance its contribution to ESG implementation while expanding financing access for more exporters.